The Analysis of Financial Performance Measurement of Global Cash Management Project Using Earned Value Analysis at PT. APRISMA INDONESIA - Aldhi Halim; Syahrial Noviananto; Tony Tony; Raymundus Parulian Sihotang (Journal of Applied Finance & Accounting, 2008)
Many components in a software house company can be used in controlling and measuring its information technology projects.  The financial component is not only the numbers that tells how a company generates its profits. It also can tell how a project performance related to its scope, cost, schedule, and quality. For example, many information technology projects’ budget increases as more work time needed to complete the planned schedule due to problems occurred whilst project execution. These correlations between cost, schedule and the execution performance can be measured from a project financial component using a method called as Earned Value Analysis. The purpose of the research is to help PT. Aprisma Indonesia to properly and comprehensively analyze the Global Cash Management financial performance and find the most feasible recommendation to improve the projects performance in the future. The result of the research is to measures on how the Global Cash Management project performed according to the time and budget plan at PT. Aprisma Indonesia. Hopefully by knowing the components that influencing the Global Cash Management project cost and understand how to measure them, PT. Aprisma Indonesia would be able to quickly execute management strategies to address specific project problems.